Cellular origin of microRNA‐371a‐3p in healthy males based on systematic urogenital tract tissue evaluation. (20th February 2019) - Boellaard, W. P. A.; Gillis, A. J. M.; van Leenders, G. J. L. H.; Stoop, H.; van Agthoven, T.; Dorssers, L. C. J.; Dinkelman‐Smit, M.; Boormans, J. L.; Looijenga, L. H. J.
Abstract: Background: The microRNA‐371a‐3p (miR‐371a‐3p) has been reported to be an informative liquid biopsy (serum and plasma) molecular biomarker for both diagnosis and follow‐up of patients with a malignant (testicular) germ cell tumor ((T)GCT). It is expressed in all histological cancer elements, with the exception of mature teratoma. However, normal testis, semen, and serum of males with a disrupted testicular integrity without a TGCT may contain miR‐371a‐3p levels above threshold, of which the cellular origin is unknown. Objectives: Therefore, a series of relevant tissues (frozen and formalin‐fixed paraffin‐embedded (FFPE), when available) from the complete male urogenital tract (i.e., kidney to urethra and testis to urethra) and semen was investigated for miR‐371a‐3p levels using targeted quantitative RT‐PCR (qRT‐PCR). Materials and methods: In total, semen of males with normospermia ( n = 11) and oligospermia ( n = 3) was investigated, as well as 88 samples derived from 32 different patients. The samples represented one set of tissues related to the entire male urogenital tract (11 anatomical locations), three sets for 10 locations, and four sets for six locations. Results: All testis parenchyma ( n = 17) cases showed low miR‐371a‐3p levels. Eight out of 14 (57%) semen samples showed detectable miR‐371a‐3p levels, irrespective of the amount of motile spermatozoa, but related to sperm concentration and matched Johnsen score (Spearman's rho correlation coefficient 0.849 and 0.871, p = 0.000, respectively). In all other tissues investigated, miR‐371a‐3p could not be detected. Discussion: This study demonstrates that the miR‐371a‐3p in healthy adult males is solely derived from the germ cell compartment. Conclusions: The observation is important in the context of applying miR‐371a‐3p as molecular liquid biopsy biomarker for diagnosis and follow‐up of patients with malignant (T)GCT. Moreover, miR‐371a‐3p might be an informative seminal biomarker for testicular germ cell composition.